An Alkaline-Stable, Metal Hydroxide Mimicking Metal-Organic Framework for Efficient Electrocatalytic Oxygen Evolution - Lu, Xue-Feng; Liao, Pei-Qin; Wang, Jia-Wei; Wu, Jun-Xi; Chen, Xun-Wei; He, Chun-Ting; Zhang, Jie-Peng; Li, Gao-Ren; Chen, Xiao-Ming (Journal of the American Chemical Society, 2016)
Postsynthetic ion exchange of [Co2(μ-Cl)2(btta)] (MAF-X27-Cl, H2bbta =1H,5H-benzo(1,2-d:4,5-d')bistriazole) possessing open metal sites on its pore surface yields a material [Co2(μ-OH)2(bbta)] (MAF-X27-OH) functionalized by both open metal sites and hydroxide ligands, giving drastically improved electrocatalytic activities for the oxygen evolution reaction (an overpotential of 292 mV at 10.0 mA cm(-2) in 1.0 M KOH solution). Isotope tracing experiments further confirm that the hydroxide ligands are involved in the OER process to provide a low-energy intraframework coupling pathway.